Revisiting Marketing Strategies for MSMEs in the Resilient Business Environment - Chandel, Kulbhushan; Sharma, Nitya (Indian Journal of Marketing, 2014)
The growth of medium, small, and micro enterprises has been the most significant feature of a planned economy. It has a unique advantage of providing high rate of employment opportunities with lesser capital investment. The MSMEs consider the design, development, branding, and positioning of the product as the most critical decision amongst all the strategic decisions to be made while designing marketing strategies. This paper attempted to investigate the influence of marketing strategies in determining the success of an enterprise while exploring market avenues for a small scale firm. The study is based on primary data collected by using a structured questionnaire. Various statistical tools like mean, standard deviation, skewness, kurtosis, chi-square, correlation, and factor analysis had been used for data analysis. Analysis of various factors influencing the internal and external business environment suggest that market aesthetics and its market demand were the most decisive factors which influenced the decision of entrepreneurs. Henceforth, it could be summated that while designing the marketing strategies for a firm, the MSMEs made an assessment of various market factors. However, the industry requires constant upgradation of information regarding the use of newer production technology and market requirements for survival in the market and for facing the global pressures. It is suggested that the entrepreneurs should recognize the use of web portals and e-marketing and also develop cartel and clusters to build the requisite infrastructural and operational facilities to come at par with international standards.